Reformulasi Kristologi Monoteistik Berdasarkan Kolose 1:15-20 dalam Menanggapi Tantangan Teologi Sekularisme - Yefta Yan Mangoli; Gabriel Nuhk Rembang (STT INTI Bandung, 2025)
This article aims to examine the historical records of the Church Fathers that gave rise to Christological issues. In response to heretical interpretations, the study seeks to explore Paul’s declaration concerning Christ as “the firstborn over all creation” in Colossians 1:15–20, and to formulate a monotheistic Christological concept in accordance with the theological message of the text. The research was conducted using a qualitative approach through literature review and textual analysis. It also employed an interpretative method of analyzing New Testament literature, particularly Paul's epistles, in order to capture the original meaning within its historical and theological context. Paul's emphasis on the supremacy of Christ in Colossians 1:15–20 reveals that Christ is not merely part of creation, but is a Divine Person actively involved in creation itself. The phrase “firstborn” is not meant chronologically or literally, but rather as a declaration of Christ’s authority and ontological superiority over all creation. This understanding is consistent with the Christian monotheistic doctrine, which affirms the divinity of Christ as the Son of God and Creator of all things (cf. John 1:3). Thus, this article concludes that the Christology presented in Colossians 1:15–20 is a firm affirmation of the divinity of Christ, standing strong within the framework of Christian monotheism.